Vicente Sotto Memorial Medical Center - Regional Heart Center A.C.T. - B.E.S.T. (A-Adult C-Cardiology Fellowship T-Training B-Built on E-Excellence, S-Social Responsibility, T-Transformative Education and T-Trust) Peri-COVID-19 organizational planning, program innovations, implementation, and evaluation - Ypil, Wilfredo Jr. M.
Cardiovascular diseases remain as the leading cause of death among Filipinos during the first half of 2023, as stated in the report by the Philippine Statistics Authority, accounting for 18% of the total deaths). (PSA, 2023) The Vicente Sotto Memorial Medical Center – Regional Heart Center (VSMMC-RHC) was designated by the Department of Health (DOH) as the designated apex Advanced Cardiovascular Care Center (ACCC). (Department of Health, 2021) Hence, the Adult Cardiology Fellowship Training Program (ACFTP) was initiated in April 2020. The COVID-19 pandemic, however, disrupted the program and challenged the attainment of the intended outcomes of the trainees. Hence, this Capstone Project was done with the aim to identify and analyze program curricular problems; and institute such modifications in the ACFTP to bridge the gaps. The crucial approach to addressing the problem is the teaching skills enhancement of the faculty trainers. A year-long Faculty Development Program (FDP) was initiated to guide the Cardiology consultant trainers in modifying the curriculum into outcome-based education (OBE), instituting innovative strategies of clinical instruction, shifting to workplace-based and Entrustable Professional Activities (EPA)- based assessments and launching the “Salig” (transl. “Trust”) Mentoring Program, which were done in four FDP courses from March 2022 to February 2023. These program changes transformed the OBE-ACFTP into the only ACFTP in the country that is EPA-based and with a formal mentoring program. The Philippine Heart Association Accreditation Committee and the Specialty Board in Adult Cardiology lauded these program innovations during their evaluation visit and granted the ACFTP a full 3-year accreditation status last May 2023. Furthermore, an initial objectives-oriented approach of program and teachers-mentors’ evaluation was done by collating feedback from the VSMMC-RHC Cardiology fellows-in-training. The VSMMC-RHC A.C.T.-B.E.S.T. (A-Adult C-Cardiology Fellowship T-Training B-Built on E-Excellence, S-Social Responsibility, T-Transformative Education and T-Trust) is committed to produce clinically competent cardiologists who are also trustworthy leaders and change agents of the community.